The Influence of Emotional Intelligence, Spiritual Intelligence on the Level of Understanding of Social and Environmental Accounting: Study of 2018-2021 Class of Accounting Students, Faculty of Economics and Business, Tadulako University - MISNAWATI, Misnawati; JURANA, Jurana; IQBAL, Mohammad; PARANOAN, Selmita; FURQAN, Andi Chairil (PT Keberlanjutan Strategis Indonesia, 2024)
Abstract This research aims to test and analyze the Direction of Emotional Intelligence, Spiritual Intelligence on the Level of Understanding of Social and Environmental Accounting. Study of 2018-2021 Class of Accounting Students, Faculty of Economics and Business, Tadulako University. This research uses a survey method, using the Slovin method sampling technique. The respondents in this research were students at Tadulako University, Faculty of Economics, majoring in Accounting, totaling 111 respondents. The research method used in this research is quantitative research using multiple linear regression data analysis, data collection techniques using questionnaires. The results of this research show that emotional intelligence and spiritual intelligence simultaneously have a significant effect on the level of understanding of social and environmental accounting. Emotional intelligence partially has a significant effect on the level of understanding of social and environmental accounting, spiritual intelligence partially has a significant effect on the level of understanding of social and environmental accounting